PARTICIPATORY FANDOM OF ARMY BTS INDONESIA IN THE DIGITAL COMIC ON WEBTOON APPS - Irwansyah, Irwansyah; Lestari, Annisa Fitriana (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2020)
The development of technology, communication and information facilitates cultural exchange in individuals and groups. One form of the phenomenon of cultural exchange is K-Pop. K-Pop has given rise to presence of idol, fans and fandom. Uses and gratification theory shows that individuals actively use the media to fulfill their goals as fans with a form of participatory fandom. In economy context, idols are used as a media consumer attraction. Idol cooperation with a media, attracted fans to participate with the media. With the presence of digital media, fans do online participatory fandom activities, such as digital comics. The features of digital comics are used by fans as a medium for participatory fandom. By making fans of BTS (ARMY BTS Indonesia) in LINE Webtoon, this research was conducted to look at patterns of fan participation with different categories in utilizing digital comic applications as fandom media. Research used constructivism paradigm through a qualitative digital ethnographic approach. Semi-structured interviews were carried out on five informants who were ARMY BTS Indonesia as readers of "Save Me" webtoon and digital observations in LINE Webtoon. The results show that there are two characteristics of fans, namely temporary fan and devoted fan. Other results show that devoted fans take advantage of the features in LINE Webtoon more optimally as a form of dedication to their idols, while temporary fans have other phenomena besides idols to do participatory fandom activities. To cite this article (7th APA style): Irwansyah & Lestari, A. F. (2020). Participatory Fandom of Army BTS Indonesia in the Digital Comic on Webtoon Apps. Journal Communication Spectrum, 10(1), 46-57. http://dx.doi.org/10.36782/jcs.v9i1.1872